The global water resources and use model WaterGAP v2.2e: description and evaluation of modifications and new features - H. Müller Schmied; H. Müller Schmied; T. Trautmann; S. Ackermann; D. Cáceres; M. Flörke; H. Gerdener; E. Kynast; T. A. Peiris; L. Schiebener; M. Schumacher; P. Döll; et al. (Geoscientific Model Development)
Water – Global Assessment and Prognosis (WaterGAP) is a modeling approach for quantifying water resources and water use for all land areas of the Earth that has served science and society since 1996. In this paper, the refinements, new algorithms, and new data of the most recent model version v2.2e are described, together with a thorough evaluation of the simulated water use, streamflow, and terrestrial water storage anomaly against observation data. WaterGAP v2.2e improves the handling of inland sinks and now excludes not only large but also small human-made reservoirs when simulating naturalized conditions. The reservoir and non-irrigation water use data were updated. In addition, the model was calibrated against an updated and extended data set of streamflow observations at 1509 gauging stations. The modifications resulted in a small decrease in the estimated global renewable water resources. The model can now be started using prescribed water storages and other conditions, facilitating data assimilation and near-real-time monitoring and forecast simulations. For specific applications, the model can consider the output of a glacier model, approximate the effect of rising CO2 concentrations on evapotranspiration, or calculate the water temperature in rivers. In the paper, the publicly available standard model output is described, and caveats of the model version are provided alongside the description of the model setup in the ISIMIP3 framework.